Inflammatory Response and Immune Regulation in Brain-Heart Interaction after Stroke - Lihua Zou; Ruquan Han (Cardiovascular Therapeutics)
Cerebrocardiac syndrome (CCS) is one of the secondary myocardial injuries after stroke. Cerebrocardiac syndrome may result in a poor prognosis with high mortality. Understanding the mechanism of the brain-heart interaction may be crucial for clinical treatment of pathological changes in CCS. Accumulating evidence suggests that the inflammatory response is involved in the brain-heart interaction after stroke. Systemic inflammatory response syndrome (SIRS) evoked by stroke may injure myocardial cells directly, in which the interplay between inflammatory response, oxidative stress, cardiac sympathetic/parasympathetic dysfunction, and splenic immunoregulation may be also the key pathophysiology factor. This review article summarizes the current understanding of inflammatory response and immune regulation in brain-heart interaction after stroke.